INFORMATION REQUIREMENTS OF POPULATION IN DIFFERENT RADIATION-HYGIENIC SITUATIONS - I. A. Zykova; S. A. Zelentsova; G. A. Arkhanguelskaia (Радиационная гигиена)
An article presents the summarization of results of long time investigations of population informative requirements in the questions of radiation protection. The investigations were carried out in the territories with different radiation-hygienic characteristics. Recommendations are proposed on the content, forms and means of the given of information needed and for enhancing of the efficient of information work with population.